Basic motor competencies in Slovak children from the 3rd and 4th grade elementary age group - Šiška, Ľuboslav; Mačura, Peter; Hubinák, Andrej; Krška, Peter; Sedláček, Jaromír; Blahutová, Anna; Zvonař, Martin; Kohútová, Katarína; Štefan, Lovro (Frontiers in Pediatrics, 2024)
Background The development of movement skills is the basic goal of physical and sports education. Their level is a determining factor in the subsequent involvement of the child in physical activities. Goal is to contribute to the knowledge of basic motor competencies (BMC) in the 3rd and 4th grade boys and girls from elementary schools. Methods We collected data from 468 children (Mage = 9.6, SD = 0.6 years; 228 girls and 240 boys) from 16 third grade and 16 fourth grade classes at ten elementary schools in different parts (central, west, north) of the Slovak Republic. The primary data on the basic motor competencies of the examined groups were obtained by means of the MOBAK-3 test battery. Construct validity was analyzed by confirmatory factorial analysis and relationships between BMC and age, gender and BMI were analyzed by structural equation modeling. Results Boys had a better performance in object movement activities than the girls p < 0.01. Situation in self-movement activities was different, girls had a better performance than boys p < 0.05. The general expectation that grade is a factor to improve the performance in basic motor competencies in the compared 3rd- and 4th-graders was not clearly fulfilled. This assumption was only confirmed in girls (object movement p < 0.05, self movement p < 0.01). Confirmatory factor analysis confirmed the two-factor structure of basic motor competencies on object-movement and self-movement, while gender, BMI and age were confirmed as significant covariances. Conclusions The theory of BMC in the 3rd- and 4th-graders at elementary schools is an appropriate method to uncover the grounds for a positive attitude to physical activities later in life.